Increase Immunity By Maintaining Health And The Environment During Covid-19 Pandemic For Community In Kampung Kenanga Kelurahan Sungai Jingah - Hendera (UMBanjarmasin, 2021)
In the implementation of a clean and healthy life in the midst of a pandemic, it is the application of healthy living in order to maintain health and the environment and increase immunity is an important thing for all people to do. However, there are still very many Indonesians who do not understand the importance of a healthy lifestyle. Especially in the community among young people who still have to be assisted. This can be done by providing benefits to health and the environment such as maintaining a clean environment, regular exercise, and eating nutritious foods. In the city community, namely the garbage village is a big problem to conquer. To deal with this waste, it will certainly never be successful if it is only dealt with unilaterally by both the community and the government. The tradition of throwing garbage in the trash is still minimal in our society. Therefore, by providing a good example by cleaning up the garbage scattered on the streets around Kenanga Village. To provide aesthetic value it is also necessary to carry out planting such as ornamental plants, food plants, cooking spices and fruit plants that can be beneficial for the community, besides that for a pandemic like this, using medicinal plants is very useful for the community to get treatment. Medically, this is supported by the ease with which it is cultivated and contains various benefits in each of these medicinal plants which can be used to increase immunity in the body.